Diffusion Tensor Imaging-Based Studies at the Group-Level Applied to Animal Models of Neurodegenerative Diseases - Müller, Hans-Peter; Roselli, Francesco; Rasche, Volker; Kassubek, Jan (Frontiers in Neuroscience, 2020)
Diffusion tensor imaging (DTI), as a technique of diffusion-weighted magnetic resonance imaging (MRI), has substantially contributed to the understanding of human and non-human microstructural brain alterations in the course of neurodegenerative diseases. Given that animal models including disease or knockout models allow for a broad spectrum of experimental manipulations not applicable to humans, the non-invasive DTI approach provides a promising tool for cross-species comparative and longitudinal investigations of the neurobiological targets and mechanisms of neurodegeneration. This overview with a systematic review focuses on the principles of DTI analysis as used in studies at the group level in living preclinical models of neurodegeneration. The translational aspect from in vivo animal models toward clinical applications in humans is covered as well as the DTI-based investigation of the non-human brains´ microstructure, the methodological issues in data postprocessing, and data interpretation at different abstraction levels. The aim of integrating DTI in multiparametric or multimodal imaging protocols will allow the interrogation of DTI data in terms of directional flow of information and may identify the microstructural underpinnings of neurodegeneration-related patterns.